ANTIBACTERIAL EFFECT OF NANNOCHLOROPSIS OCULATA AS ROOT CANAL STERILIZATION MATERIAL ON STREPTOCOCCUS MUTANS BIOFILM - Soesilo, Diana; Puspita, Sinta; Christabel, Phebe Fedora (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Streptococcus mutans in the most frequent microbiota that causes pulp necrosis because of caries. The microorganism that is colonized and embedded in the biofilm matrix is resistant to antimicrobials compared to planktonic cells. Root canal sterilization materials must have good biocompatibility with tissues. Nannochloropsis oculata is an algae that contains various compounds such as terpenoids, alkaloids, and flavonoids that have potential as antibacterial and antioxidant and can be used as alternative to root canal sterilization. Method: This research was true experimental laboratory research with post-test only control group design. The antibacterial potential of Nannochloropsis oculata was tested using the biofilm method, divided into 5 groups. The control group was: K- (aquadest), K+ (calcium hydroxide), and the treatment group was given Nannochloropsis oculata: P1 (0.625%), P2 (1.25%), and P3 (2.5 %). Congo Red method test was to determine the formation of biofilm that shows black strains on agar. While biofilm test with Microtiter Plate Assay to measure the value of biofilm that were inhibited in Optical Density (OD) value in the ELISA Reader. The lower the value, the more biofilm inhibited, with OD value, inhibition percentage could counted Result: The result of all treatment groups were increasing in percentage inhibition value shows inhibition in biofilm growth (p <0.05). Conclusion: Nannochloropsis oculata had an antibacterial effect on the biofilm of Streptococcus mutans